Nitrofurantoin Pulmonary Toxicity: A Brief Review - Vahid, Bobbak; Wildemore, Bernadette M.M. (Current Respiratory Medicine Reviews, 2006)
Nitrofurantoin is an antimicrobial agent that is commonly used for the treatment of recurrent urinary tract infection. Nitrofurantoin pulmonary toxicity can present as acute, subacute, or chronic respiratory disease. Common manifestations are dry cough, chest pain, dyspnea, and hypoxemia. Skin rash, arthralgia, and abnormal transaminases are occasionally present. Chest imaging shows patchy infiltrates and fibrosis. Treatment includes discontinuing the medication. Although the role of corticosteroids has not been well described, patients with respiratory symptoms or hypoxemia may benefit from a trial of corticosteroid therapy.
Keywords: drug-induced lung toxicity